Digital Humanism In Education: Balancing Artificial Intelligence And Ethical Pedagogy For The 21st Century Classroom - Muhsinin (CV. SINAR HOWUHOWU, 2025)
The rapid advancement of Artificial Intelligence (AI) has reshaped educational landscapes across the globe, offering new opportunities for personalized learning, data-driven assessment, and intelligent tutoring systems. However, this technological acceleration also presents ethical and pedagogical dilemmas regarding the role of human values, empathy, and moral reasoning in education. This paper explores the concept of Digital Humanism in Education, proposing a balanced framework that integrates technological innovation with human-centered pedagogy. Using a mixed-method design, the study examines teachers’ perceptions and practices across Southeast Asian higher education institutions, focusing on how AI-driven tools influence pedagogical decision-making and learner autonomy. The results reveal that while educators acknowledge AI’s capacity to enhance efficiency and inclusivity, they also express concern over its potential to depersonalize learning and erode moral engagement. This study argues that ethical literacy, emotional intelligence, and critical digital pedagogy must accompany technological integration to sustain the human essence of education. By advancing a model of ethical AI pedagogy, this research contributes to reimagining 21st-century education as both technologically empowered and deeply human-centered.